Impact of the Covid pandemic on timely cancer diagnosis across European healthcare settings: a scoping review - Pennisi, Flavia; Odelli, Stefano; Borlini, Stefania; Morani, Federica; Signorelli, Carlo; Renzi, Cristina (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Introduction. The COVID-19 pandemic presented unprecedented challenges to European healthcare systems. The study aimed to review the available evidence on the impact of the pandemic on the timely diagnosis of cancer across European countries. The primary objective was to examine changes in diagnostic pathways and stage at diagnosis during the pandemic, compared to the pre-pandemic period, across European countries, taking healthcare system characteristics and COVID-19 policies into account. Methods. We conducted a review of the impact of the pandemic on cancer diagnosis in Europe, analyzing primary studies from 2018 to 2023 using both quantitative and qualitative methods through searches in PubMed and Scopus databases. Study quality was assessed using the Mixed Methods Appraisal Tool. The main explanatory factors analyzed were grouped into two categories: Covid-policies (government responses, using the Oxford COVID-19 Government Response Tracker and its stringency index as key metrics) and healthcare characteristics (healthcare system models, expenditure and resources, including hospital beds and the ratio of medical doctors). Study design. Scoping review.Results. Overall, 127 papers were screened, 80 retrieved for full-text evaluation and 50 articles were included in the review. The studies encompassed a total of 509,753 patients from 17 European countries.  The pandemic period was characterised by worse process and outcome measures for all examined cancers, except for lung cancer, compared to the pre-pandemic period. Grouping countries based on government actions and policy responses (stringency index) did not show any differences in timely cancer diagnosis. Countries with lower healthcare expenditure (per capita expenditure 20% of General Practitioners over the total number of physicians and with more hospital beds per population experienced fewer diagnostic delays during the pandemic.Conclusions. Overall, the review suggests that diagnostic pathways and cancer stage at diagnosis during the COVID-19 pandemic varied across Europe, with countries’ healthcare expenditure, investments in prevention, the proportion of General Practitioners and the number of hospital beds per population possibly playing a role. This analysis can inform healthcare policies aimed at addressing post-pandemic challenges and formulating resilience plans for future emergencies.